Lymnaea cubensis, an experimental intermediate host for Fascioloides magna - Vignoles, Philippe; Novobilský, Adam; Höglund, Johan; Kašný, Martin; Pankrác, Jan; Dreyfuss, Gilles; Pointier, Jean-Pierre; Rondelaud, Daniel (Folia parasitologica, 2014)
Single-miracidium infections of Lymnaea cubensis (Pfeiffer) from Guadeloupe with the giant liver fluke Fascioloides magna (Bassi, 1875) (Digenea) were carried out during five successive snail generations to determine if this lymnaeid might sustain complete larval development of the parasite. Controls were constituted by a French population of Galba truncatula (Miller) (a single generation) infected according to the same protocol. It was recorded that prevalence and intensity of F. magna infection in L. cubensis progressively increased from F1 to F5 generations. Cercarial shedding of F. magna was noted only within F5 generation of L. cubensis. However, most measured parameters of infection in this species were significantly lower than those noted for G. truncatula and most L. cubensis died after a single shedding wave. Despite this, L. cubensis can be added to the list of potential intermediate hosts of F. magna.
Keywords: Animals; Lymnaea; Fasciolidae; zvířata; Host-Parasite Interactions; interakce hostitele a parazita